Penerapan Program Kampus Mengajar Angkatan VI Bertujuan Untuk Meningkatkan Kemampuan Literasi dan Numerasi - Hidayat, Hidayat; Muhajir, Muhajir; Sari, Dira Pustita; Tartiyoso, Seget; Helman, Helman (Yayasan Literasi Sains Indonesia, 2024)
The Teaching Campus Program is part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative which aims to provide opportunities for students to be directly involved in assisting the learning process in elementary schools. This research focuses on the implementation of the Teaching Campus Program at SD Negeri 020276 Binjai. Participating students play an important role in supporting teaching and learning activities, assisting in the use of technology, and increasing student motivation and interest in learning, especially in literacy and numeracy. This program is expected to provide benefits for both students and schools. Students can increase social awareness, develop thinking and collaboration skills, and broaden their horizons and character. Meanwhile, schools get additional support in the learning process and improving the quality of education. This research uses a qualitative approach with data collection methods in the form of observation, interviews, and documentary studies. The results showed that the Teaching Campus Program had a positive impact on student motivation and interest in learning. The presence of students provides variety in the learning process and increases interaction between students and teachers. In addition, this program also provides opportunities for students to apply their knowledge directly in the field, as well as develop their professional skills. It is hoped that the Teaching Campus Program can continue to be implemented and improved to provide greater benefits for education in Indonesia